Strengthening The Role Of The Village In The Preservation Of Customs During The Covid-19 Pandemic - Sofa Marwah (Faculty of Social and Political Sciences, Universitas Diponegoro, 2021)
This article aims to investigate the policy shift of local cultural management in Banyumas Regency during the Covid-19. The pandemic has brought a wide impact beyond the health issues including cultural activities that tend to be overlooked. The local culture of Banyumas was selected because local cultures other than Javanese somehow failed to be noticed by the experts since the New Order Era. This paper is library research that examines cultural policies. The result reveals that the Banyumas local culture has been managed by the local government of Banyumas through the culture and tourism office. In cultural activities, there are two patterns, namely cultural activities held by the Banyumas Regency government and cultural activities held by the village administration. During the pandemic, nonetheless, more activities are carried out by the village administration and local society. It shows that the social-cultural bond between the local people and the village administration is strong in the attempt of preserving their customs and traditions. The value of mutual assistance is a pivotal contribution to support the cultural activities amid the less favorable situation due to the Covid-19 pandemic. This outcome also confirms that a study of cultural policy cannot be separated from the necessity of understanding how the village administration as the lowest government unit plays a significant role in cultural preservation along with the local society.